1997
DOI: 10.1590/s0066-782x1997000700006
|View full text |Cite
|
Sign up to set email alerts
|

Enalaprilato na prevenção da hipertrofia ventricular esquerda induzida pelo isoproterenol

Abstract: Enalaprilat inhibited the isoproterenol action on the cardiomyocite, avoiding partially the LVH and decreasing the content of collagen fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The investigations included in Table 1 demonstrate the relevance of angiotensin-converting enzyme (ACE) inhibitors14,15,2224 and angiotensin antagonist25 treatment for cardiac hypertrophy regression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigations included in Table 1 demonstrate the relevance of angiotensin-converting enzyme (ACE) inhibitors14,15,2224 and angiotensin antagonist25 treatment for cardiac hypertrophy regression.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, ACE inhibitors have shown promising cardio-protective effects in experimental models of hypertensive heart disease;22 specifically, these inhibitors improve micro-vascular ischemia, ventricular function and arrhythmias 14–16, 23–29. We have previously reported that enalapril14 (ACE inhibitor) and verapamil23 (Ca ++ channel blocker) provide the same cardio-protector response in an isoproterenol-induced LVH model in rats 28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertrophic cardiomyopathy may be defined as myocardial involvement without definitive etiology, characterized by left ventricle hypertrophy (rarely right ventricle), with myofibrillar disorder, increased left ventricular ejection fraction and decreased cardiac output, which depends on the functional impairment degree [41-47]. The outflow tract obstruction may exist or not.…”
Section: Discussionmentioning
confidence: 99%